PELATIHAN MOTIVASI RISK-UNCERTAINTY-HOPE UNTUK ETOS KERJA - Riyono, Bagus; Indrayanti (JIP (Jurnal Intervensi Psikologi), 2023)
Work motivation, defined as a society's attitude towards the meaning of work or positive work values in an individual, is targeted for enhancement through a training program. This intervention utilizes the RUH (Risk, Hope, and Uncertainty) theoretical framework to foster work ethic motivation. The program involved 56 participants, including MSME entrepreneurs, teachers, village officials, and members of PKK and KWT groups. Employing an experimental method with pre-test and post-test assessments, data analysis relied on thematic analysis. The research findings indicate an improvement in work ethic, evident in the post-test themes reflecting enhanced hope and perseverance in addressing challenges. The shifts in participants' perspectives and attitudes signify that RUH motivation training increases their preparedness for uncertainty, heightens awareness of job risks, and fosters hope in approaching their work.